A taxonomic study on the genus Stichillus (Diptera: Phoridae) from South Korea, with a key to species from East Asia - Lee, Jun-Ho; Kim, Sam-Kyu (Zootaxa, 2023)
The South Korean species of the genus Stichillus Enderlein are reviewed and four species are newly recognized. One of them, S. koreanus sp. nov., is described as new to science and the other three species, viz. S. cylindratus Nakayama & Shima, S. japonicus (Matsumura) and S. spinosus Liu & Chou are new to South Korea. Detailed descriptions with photographs of four Korean Stichillus species, and a revised key to males of ten species from East Asia except Mongolia and North Korea are provided.